APPLICATION OF NATURAL FIBER FOR SHORT TERM STABILIZATION OF MARINE CLAY SLOPE - Ahmad, M.M.; Zainol, N.Z.; Ab Manaf, M.B.H.; Faisal, A.; Mohd Zahid, M.Z.A. (Journal of Advanced Manufacturing Technology (JAMT), 2020)
Existence of marine clay in civil engineering field leading to further investigation on the properties as well as the method of stabilization. The aim of this study is to investigate the shear strength parameter of marine clay slope stabilized with kenaf fiber. Laboratory testing has been conducted to determine the marine clay and stabilized marine clay properties and its characteristic by using soil classification of particle size distribution, specific gravity, Atterberg limit and unconfined compression test. The result shows that the shear strength of marine clay reinforced with kenaf fiber is improved by increasing the percentage of kenaf fiber mixed into marine clay soil. The safety factor obtained from slope stability analysis shows that addition of kenaf fiber to the marine clay soil improves the marine clay slope stability. By adding 5% and 10% of kenaf fiber improves safety factor to more than 1.2 as required for most of temporary slope construction.